L2 reading motivation among students of UiTM Jengka / Rosita Aminullah and Caroline Joseph - Aminullah, Rosita; Joseph, Caroline (2012)
This paper examines the affective factors that influence L2 reading motivation among UiTM Jengka students. A study was conducted using a set of questionnaires which had been developed by Nishino (2005) and adapted from Mari's (2002). The results of the study show that L2 reading motivation among UiTM Jengka students are influenced by a number of factors. It is not influenced by gender or socio-economic status but by their task specific self-concept which is positively related with expectancies for success, how they interpret past events, and how they perceive attitudes and expectations of others. The students are found to be motivated to read in English because they want to succeed in life.